Новый вид рода Entomelas Travassos, 1930 (Nematoda, Rhabdiasidae)—паразит легких желтопузика - Шарпило, В.П.; Ваккер, В.Г. (Вестник зоологии, 1972)
The new species Entomelas kazachstanika is described, parasitizing in lungs of Ophisaurus apodus (P all.) in the Crimea, Transcaucasia and Middle Asia. The new species differs from the closest — one E. dujardini (M a u p a s in S e u r a t, 1916) in considerably less quantity of eggs without larvae, in much less body width, strongly developed glands concentrated in the oesophagus zone and anterior part of the intestine, non-pigmented content of the intestine and other characters. A host of the new species differs in its ecology from that of E. dujardini.